Phytoseiidae (Acari: Mesostigmata) from the atlantic forest in Rio de Janeiro, Brazil, with complementary description of amblyseius impeltatus Denmark & Muma - Cavalcante, Ana Cristina Cerqueira; Demite, Peterson Rodrigo; Lofego, Antônio Carlos [UNESP]; Hernandes, Fabio Akashi (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2021)
Phytoseiid mites (Acari: Phytoseiidae) have been largely used for the biological control of arthropod pests. However, information on the phytoseiid fauna associated with plants of the Rio de Janeiro State, Brazil is still scanty. Surveys were carried out in two areas of Atlantic Forest in Rio de Janeiro State – Jaguanum island and Paraty. We report 11 species of seven genera from all three subfamilies. A complementary re-description is provided for Amblyseius impeltatus Denmark & Muma, 1973 and measurements are provided for ten other species.
Keywords: Coast; Island; Parasitiformes; Predator; Survey